Peran Keunggulan Bersaing Memediasi Pengaruh Inovasi Bisnis dan Promosi Media Sosial terhadap Kinerja Pemasaran - Guntara, Alpin Angga; Yasa, Ni Nyoman Kerti (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This research seeks to explain how competitive advantage mediates the effects of business innovation and social media promotion on the marketing performance of the Ate handicraft industry in Karangasem Regency. The study’s population includes all Ate artisans in Karangasem, with a sample of 140 artisans selected through purposive sampling. Path analysis using SEM-PLS was applied. The findings show that both business innovation and social media promotion have a significant positive effect on marketing performance. Additionally, business innovation and social media promotion positively and significantly influence competitive advantage, which in turn significantly improves marketing performance. Competitive advantage also partially mediates the impact of business innovation and social media promotion on marketing performance. Thus, it is essential for Ate craftsmen in Karangasem to continuously enhance business innovation and social media promotion to boost their competitive edge and marketing performance.